Pyridoxal phosphate site in glycogen phosphorylase b: structure in native enzyme and in three derivatives with modified cofactors. - Oikonomakos, N; Johnson, L; Acharya, K; Stuart, D; Barford, D; Hajdu, J; Varvill, K; Melpidou, A; Papageorgiou, T; Graves, D (1987)
The detailed environment of the essential cofactor pyridoxal 5'-phosphate in glycogen phosphorylase b, resulting from crystallographic refinement at 1.9-A resolution, is described. The pyridoxal ring is buried in a nonpolar site containing three aromatic rings while the 5'-phosphate group is highly solvated and makes only three direct contacts to the protein. The pyridine nitrogen interacts via a water with protein atoms [main chain carbonyl oxygen (Asn-133) and OH of tyrosine (Tyr-90)]. The crystal structures of three active derivatives of phosphorylase reconstituted with 5'-deoxypyridoxal 5'-methylenephosphonate (PDMP), 6-fluoropyridoxal 5'-phosphate (6-FPLP), and pyridoxal (PL) in place of the natural cofactor have been determined at 2.5-A resolution. The results for PDMP-phosphorylase show a closer proximity of the phosphonate group to the NZ atom of a lysine (Lys-574) than that observed in the native enzyme, consistent with 31P NMR studies that have shown a change in ionization state of the phosphonate group compared to the native cofactor phosphate. The replacement of the polar 5'-ester linkage by a CH2 group results in a small shift of a water and its hydrogen-bonded tyrosine (Tyr-648). In 6-FPLP-phosphorylase the fluorine is accommodated with no significant change in structure. It is suggested that substitution of the electronegative fluorine at the 6-position may result in lower activity of 6-FPLP-phosphorylase through a strengthening of hydrogen-bonded interactions to the pyridine nitrogen N1.(ABSTRACT TRUNCATED AT 250 WORDS)